2010
DOI: 10.1016/j.jcat.2010.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Steam reforming of methanol on PdZn near-surface alloys on Pd(1 1 1) and Pd foil studied by in-situ XPS, LEIS and PM-IRAS

Abstract: The CO2-selectivity in methanol steam reforming was investigated for a "multilayer" PdZn 1:1 surface alloy (thickness of ~1.3 nm) and for a subsurface-Zn diluted "monolayer" PdZn surface alloy, both exhibiting a 1:1 composition in the surface layer. Despite having almost the same surface layer stoichiometry, these two types of near-surface alloys exhibit different corrugations and electronic structures. The CO2-selective multilayer alloy features a lowered density of states close to the Fermi edge and surface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
40
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 70 publications
(50 citation statements)
references
References 49 publications
(131 reference statements)
5
40
1
Order By: Relevance
“…11,26 Most importantly, the density of states (DOS) near the Fermi level changes, evident from the valence band ( Figure 5C), which suggests a "Cu-like" electronic structure with lower DOS close to the Fermi level. 14,20,24 The similarity of effects detected by FTIR and XPS confirms the good comparability of model and applied PdZn bimetallic catalysts and is corroborated by DFT. 23 The different electronic structure of PdZn and Pd clearly affects the adsorption of reactants and intermediates, thus modifying catalysis.…”
Section: Casesupporting
confidence: 58%
“…11,26 Most importantly, the density of states (DOS) near the Fermi level changes, evident from the valence band ( Figure 5C), which suggests a "Cu-like" electronic structure with lower DOS close to the Fermi level. 14,20,24 The similarity of effects detected by FTIR and XPS confirms the good comparability of model and applied PdZn bimetallic catalysts and is corroborated by DFT. 23 The different electronic structure of PdZn and Pd clearly affects the adsorption of reactants and intermediates, thus modifying catalysis.…”
Section: Casesupporting
confidence: 58%
“…Ultimately, these results confirm previous studies on related model systems wherein oxidized Zn species have been clearly identified by in situ Xray photoelectron spectroscopy as being present in the CO 2selective state of the catalyst, and as being capable of efficient water activation, a prerequisite for a CO 2 -selective catalyst. [12,[14][15][16] Nevertheless, XPS is often not suitable for exploring supported catalysts such as ZnPd/ZnO, because of the induced charging on insulating samples and the excess of ZnO that makes it impossible to identify ZnO patches formed in situ. This is the first time that the selective state of a ZnPd/ZnO catalyst is made clearly visible and is shown to contain special interfacial sites, where uncovered intermetallic ZnPd particles and ZnO coexist in close proximity.…”
Section: Methodsmentioning
confidence: 99%
“…[12] The presence of oxidized Zn in near-surface regions has been shown to be inevitably linked to a high CO 2 -selectivity in inverse model catalyst studies of near-surface intermetallic phases. [14][15][16] The knowledge transfer from these model systems to high-performance catalysts represents a great step towards understanding MSR.…”
Section: Matthias Friedrich Simon Penner Marc Heggen and Marc Armbmentioning
confidence: 99%
“…A variety of vibrational spectroscopy methods were utilized to follow the reactant to product transformation [35,36]. Among these methods are surface sensitive techniques such as SFG (sum frequency generation) vibrational spectroscopy [32,37] and PM-IRAS (polarization modulation infrared reflection absorption spectroscopy) [38,39] that detect active intermediates during catalytic reactions. Time resolved IR spectroscopy measurements analyze the kinetic properties of catalytic reactions [40,41] while IR microspectroscopy can track the spatial distribution of reactants and products within the catalyst [42][43][44].…”
Section: Advanced Instrumentation For In Situ Characterization Of Catmentioning
confidence: 99%